Association Between Weight Change and Leukocyte Telomere Length in U.S. Adults - Zhang, Yiling; Xu, Ziye; Yang, Yiling; Cao, Shanshan; Lyu, Sali; Duan, Weiwei (Frontiers in Endocrinology, 2021)
Objective: To investigate the association of dynamic weight change in adulthood with leukocyte telomere length among U.S. adults. Methods: This study included 3,886 subjects aged 36 75 years from the National Health and Nutrition Examination Survey (NHANES) 1999–2002 cycle. Survey-weighted multivariable linear regression with adjustments for potential confounders was utilized. Results: 3,386 individuals were finally included. People with stable obesity had a 0.130 kbp (95% CI: 0.061 0.198, P=1.97E-04) shorter leukocyte telomere length than those with stable normal weight (reference group) during the 10-year period, corresponding to approximately 8.7 years of aging. Weight gain from nonobesity to obesity shortened the leukocyte telomere length by 0.094 kbp (95% CI: 0.012 0.177, P=0.026), while normal weight to overweight or remaining overweight shortened the leukocyte telomere length by 0.074 kbp (95% CI: 0.014 0.134, P=0.016). The leukocyte telomere length has 0.003 kbp attrition on average for every 1 kg increase in weight from a mean age of 41 years to 51 years. Further stratified analysis showed that the associations generally varied across sex and race. Conclusions: This study found that weight change in 10-year period was associated with leukocyte telomere length and supports the theory that weight gain promotes aging across adulthood.